Adaptation of a health literacy screener for computerized, self-administered use by U.S. adults - Olivia J. Lindly; Taylor A. Wahl; Noa M. Stotts; Amy M. Shui (Elsevier, 2024)
Objective: Health literacy is a critical health determinant, for which few computerized, self-administered assessments exist. This study adapted and tested the reliability of the Newest Vital Sign© (NVS) as a computerized, self-administered health literacy screener. Methods: Phase one involved 33 participants to create response options for a computerized, self-administered NVS (C-NVS). Phase two was a randomized crossover trial to test the consistency of C-NVS and original, interviewer-administered NVS (I-NVS) scores in 89 participants. Results: Linear mixed-effects regression model results showed a significant carryover effect (p < .001). Crossover trial data from time 1 showed that participants who initially received the C-NVS had significantly higher average scores (M = 5.7, SD = 0.6) than participants who received the I-NVS (M = 4.5, SD = 1.5; t(87) = 5.25, p < .001). Exploratory analysis results showed that when the washout period was longer than 33 days (75th percentile) the carryover effect was not statistically significant (p = .077). Conclusion and innovation: Findings suggest learning can occur when health literacy screeners are administered more than once in less than a month's time and computerized, self-administered health literacy screeners may produce ceiling effects. A universal precautions approach to health literacy therefore remains germane.